Validity of Science Literacy-Oriented E-Lapd on Chemical Equilibrium Materials Using Problem-Based Learning Models - Anggraeni, Yunita; Muchlis, Muchlis (International Journal of Educational Research, 2025)
This study aims to obtain the validity of E-LAPD using the Problem Based Learning (PBL) model that can be used to improve science literacy on chemical equilibrium material. The design used is a 4-D model designed to improve students' science literacy skills. The valid E-LAPD was evaluated through a validation sheet filled in by the validator using a Likert scale. Validity consists of construct validity which includes presentation components, graphic components, suitability of models and indicators to be improved and content validation which includes the suitability of learning objectives with learning outcomes and the suitability of problems or phenomena with the material being taught. The validity of E-LAPD is declared valid if the score from the validator is at least 4 and does not have one score < 3 from the validator. The results showed that the E-LAPD developed had high validity indicating that the mode score of the validator ≥ 4. The developed E-LAPD was declared valid for use with a construct and content validation assessment which was described as valid with a score of 4, thus E-LAPD using the PBL model was declared valid for use to improve science literacy in chemical equilibrium material.